Theoretical studies on the Annexin A1-S100A11 Heterotetramer and Platinum-Mediated C-H Activation Pathways - Sanchez, Wesley Andres (East Carolina University, 2023)
Computational chemistry is a powerful tool for characterizing chemical phenomena when they are difficult to observe in laboratory settings or simply elusive. By employing the fundamental equations of nature, computational chemistry simulates a system's behavior through efficient computer programs and algorithms. In this work, two computational approaches were used to investigate biologically important systems. In Chapter 3, molecular dynamics simulations were performed on the Annexin A1-S100A11 heterotetramer. Annexins are important calcium binding proteins which have implications in calcium-regulation and numerous pathologies including many types of cancer. Annexin-A1 is known to interact with S100A11 to form a heterotetramer which is involved in regulating EGFR and thus tumor growth. In this work, the Annexin A1-S100A11 heterotetramer was modeled for the first time and subjected to multiple MD simulations to characterize the complex on the atomic level. Principle component analysis revealed three conformations of the Annexin N-terminus stemming from a kink formed through W12's interaction with M63. We identified a consistent, stable binding mode between the first 11 residues of A1 and S100A1 which was consistent to available crystal structures for A1-S100A11 and A2-S100A10. This work suggests that this stable binding mode is potentially a theme for other Annexin-S100 complexes and that the flexibility of the A1-ND affords multiple possible conformations of the A1t. In Chapters 4 and 5, quantum mechanics calculations were performed in conjunction with the Nudged Elastic Band method to investigate the mechanisms of platinum mediated C-H activation. Direct conversion of C-H bonds into other bond types is inherently difficult owing to the inertness of standard C-H bonds. In recent years, transition metal-catalyzed C-H functionalization has grown in popularity due to its numerous applications in pharmaceuticals and chemical industry. Due to their versatile electronic properties, platinum complexes have found applications ranging from OLED technology to medical imaging and anticancer treatments. In this work, computational approaches were employed on two pathways: 1) Pt-catalyzed C-H acylation of 2-(2-methylphenoxy)-pyridine and 2) solvent-controlled sp2/sp3 C-H activation of N-methyl-N-phenyl-6-(1H-pyrazol-1-yl)pyridine-2-amine. In the former, ligand exchange for cis isomers was found to be kinetically favored which was congruent with experimental observations. In the latter, several key intermediates were identified for solvent-controlled cycloplatination reactions. With a catalytic water molecule, a significant reduction in energy barrier was observed for sp2 reactions. Additionally, water was observed to facilitate a square pyramidal intermediate via oxidative addition to the platinum center in sp3 pathways.
Keywords: Nudged Elastic Band; Mechanistic studies; Computational chemistry; Molecular dynamics; Biophysics; Quantum chemistry